INFLUENCE OF DRAWING OF STEEL CARBONACEOUS WIRE ON COEFFICIENT OF CONTACT FRICTION - Ju. L. Bobarkin (Litʹë i Metallurgiâ, 2011)
Influence of degree of deformation and speed of thin drawing using water-emulsion metal-cutting compound on size of coefficient of a contact friction is investigated.